Best Answer

secx = 1/cosx

and 1/cotx = tanx, therefore

1/cosx + tanx = 1 + sinx/cosx, and

sin/cos = tanx, therefore

1/cosx + tanx = 1 + tanx, therefore

1/cosx = 1, therfore

1 = cosx.

So, therfore, it is not neccesarily true.

But if you mean

secx plus 1 divided by cotx equals (1 plus sinx) divided by cosx(this is probably what you mean) Let's start over!

secx = 1/cosx

and 1/cotx = tanx, therefore

1/cosx + tanx = (1+sinx)/cosx therefore

1/cosx + tanx = 1/cosx + sinx/cosx

sinx/cosx = tanx therfore

1/cosx + tanx = 1/cosx + tanx

Do you think this is correct? Subtract both sides by 1/cosx + tanx:

0 = 0

So, therefore, this is correct!

(BTW, I'm in Grade 6! :P)

🦃

🤨

😮

Study guides

Q: How does secx plus 1 divided by cotx equal 1 plus sinx divided by cosx?

Write your answer...

Submit

Related questions

There is no sensible or useful simplification.

(tanx+cotx)/tanx=(tanx/tanx) + (cotx/tanx) = 1 + (cosx/sinx)/(sinx/cosx)=1 + cos2x/sin2x = 1+cot2x= csc2x This is a pythagorean identity.

2

(1-cosx)/sinx + sinx/(1- cosx) = [(1 - cosx)*(1 - cosx) + sinx*sinx]/[sinx*(1-cosx)] = [1 - 2cosx + cos2x + sin2x]/[sinx*(1-cosx)] = [2 - 2cosx]/[sinx*(1-cosx)] = [2*(1-cosx)]/[sinx*(1-cosx)] = 2/sinx = 2cosecx

NO, sinxtanx=sinxsinx/cosx since tanx is sinx/cosx this is sin^2xcosx now add cosx cosx(sin^2x+1) after factoring Does this equal tanx? No, since this would require tanx to equal cosx(sin^2x+1) and it does not.

2

The differentiation of sin x plus cosx is cos (x)-sin(x).

The differentiation of sin x plus cosx, yields cos(x)-sin(x).

The derivative is 1/(1 + cosx)

to simplify Cosx=Sinx Tanx you should remember your fundamental and pythagorean identities.. Cosx + Sinx Tanx Cosx + Sinx (Sinx/Cosx) <---------- From Tanx= Sinx/Cosx Cosx + Sin2x/ Cos x <------------- do the LCD Cosx (Cosx/Cosx) + Sin2x/Cosx (Cos2x+Sin2x)/Cosx 1/Cosx <--------- From Sin2x + Cos2x =1 or Secx <-------- answer Comment if you have questions...:))

You will have to bear with the angle being represented by x because this browser will not allow characters from other alphabets!sin^2x + cos^2x = 1=> sin^2x = 1 - cos^x = (1 + cosx)(1 - cosx)Divide both sides by sinx (assuming that sinx is not zero).=> sinx = (1 + cosx)(1 - cosx)/sinxDivide both sides by (1 - cosx)=> sinx/(1 - cosx) = (1 + cosx)/sinx=> sinx/(1 - cosx) - (1 + cosx)/sinx = 0

it is not possible to get the Integral of cos2x log cosx-sinx coax plus since there are no symbols given in the equation.

(sin x + cos x) / cosx = sin x / cos x + cosx / cos x = tan x + 1

negative sin(x)

4 divided by -7

The way you have written this makes it impossible to evaluate. what math operation is involved after cosx plus 1? is that added, subtracted, multiplied or divided by 2 cos2x-3cos2 etc.

7 plus 7 divided by 7 plus 7 times 7 minus 7 is equal to 50.

sin2x / (1-cos x) = (1-cos2x) / (1-cos x) = (1-cos x)(1+cos x) / (1-cos x) = (1+cos x) sin2x=1-cos2x as sin2x+cos2x=1 1-cos2x = (1-cos x)(1+cos x) as a2-b2=(a-b)(a+b)

f(x)=sinx+cosx take the derivative f'(x)=cosx-sinx critical number when x=pi/4

x = 3pi/4

3,000 plus 596 divided by minus 100 is equal to 2,994.04

Six plus 18 divided by 3 times 4 is equal to 30.

no

0.515152

77.67